2021
DOI: 10.1029/2020gl090305
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Frost Weathering Across Unglaciated North America During the Last Glacial Maximum

Abstract: In unglaciated terrain, the imprint of past glacial periods is difficult to discern. The topographic signature of periglacial processes, such as solifluction lobes, may be erased or hidden by time and vegetation, and thus their import diminished. Belowground, periglacial weathering, particularly frost cracking, may have imparted a profound influence on weathering and erosion rates during past climate regimes. By combining a mechanical frost‐weathering model with the full suite of Last Glacial Maximum climate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 71 publications
(117 reference statements)
0
36
0
Order By: Relevance
“…In landscapes like central Appalachia, with moderate slopes and erosion rates, periglaciation likely has the most enduring impact on landscape form and Quaternary erosion rates. Periglacial erosion likely influenced landscapes south of the LIS lacking diagnostic surface features (Marshall et al., 2021; West et al., 2013) such as in the Potomac River basin, where topsoils were stripped during the LGM (Portenga et al., 2019). Outside of North America, similar dynamics may exist on periglacial landscapes like the Snowy Mountains in southern Australia (36°S), where moderately steep slopes (15–20°) preserve Pleistocene blockfields (Barrows et al., 2004) and modern soil erosion rates are a relatively slow at ∼25 m/Myr (Stromsoe et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In landscapes like central Appalachia, with moderate slopes and erosion rates, periglaciation likely has the most enduring impact on landscape form and Quaternary erosion rates. Periglacial erosion likely influenced landscapes south of the LIS lacking diagnostic surface features (Marshall et al., 2021; West et al., 2013) such as in the Potomac River basin, where topsoils were stripped during the LGM (Portenga et al., 2019). Outside of North America, similar dynamics may exist on periglacial landscapes like the Snowy Mountains in southern Australia (36°S), where moderately steep slopes (15–20°) preserve Pleistocene blockfields (Barrows et al., 2004) and modern soil erosion rates are a relatively slow at ∼25 m/Myr (Stromsoe et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Rempel et al [2016] developed a thermo-mechanical model based on the model by Walder and Hallet [1985] to incorporate ice physics without losing applicability at geomorphic scales. Marshall et al [2021] applied the model in combination with climate simulations to model frost weathering in unglaciated North America during the Last Glacial Maximum. The different models use air temperature as a proxy for rock temperature [e.g.…”
Section: Accepted Articlementioning
confidence: 99%
“…Recently, Rempel et al (2016) developed a thermo-mechanical model based on the model by Walder and Hallet (1985) to incorporate ice physics without losing applicability at geomorphic scales. Marshall et al (2021) applied the model in combination with climate simulations to model frost weathering in unglaciated North America during the Last Glacial Maximum. The different models use air temperature as a proxy for rock temperature (e.g., Hales & Roering, 2007;Rempel et al, 2016), but previous permafrost studies demonstrated that there is a significant temperature offset between air and rockwall temperature (e.g., Hasler, Gruber, & Haeberli, 2011;Magnin et al, 2015).…”
mentioning
confidence: 99%
“…Under the current climate regime, regolith production is minimal, but must have been substantially higher during the late Pleistocene for the colluvial mantles to have formed. Lower Pleistocene temperatures were probably not sufficient to increase physical weathering by frost shattering (Marshall et al, 2021). We conclude that the wetter late Pleistocene climate was conducive to accelerated mechanical weathering by climate-dependent subcritical cracking processes (Eppes and Keanini, 2017).…”
Section: Climatic Influences On Slope Soil-geomorphic Processesmentioning
confidence: 80%